Bacteria in Nanoparticle Synthesis: Current Status and Future Prospects. (29th October 2014) - Iravani, Siavash
Abstract : Microbial metal reduction can be a strategy for remediation of metal contaminations and wastes. Bacteria are capable of mobilization and immobilization of metals and in some cases, the bacteria which can reduce metal ions show the ability to precipitate metals at nanometer scale. Biosynthesis of nanoparticles (NPs) using bacteria has emerged as rapidly developing research area in green nanotechnology across the globe with various biological entities being employed in synthesis of NPs constantly forming an impute alternative for conventional chemical and physical methods. Optimization of the processes can result in synthesis of NPs with desired morphologies and controlled sizes, fast and clean. The aim of this review is, therefore, to make a reflection on the current state and future prospects and especially the possibilities and limitations of the above mentioned bio-based technique for industries.